Intravenous N-acetylcystine: the treatment of choice for paracetamol poisoning. Issue 6198 (3rd November 1979) - Prescott, L F; Illingworth, R N; Critchley, J A; Stewart, M J; Adam, R D; Proudfoot, A T
Abstract : One hundred cases of severe paracetamol poisoning were treated with intravenous N-acetylcysteine (acetyl-cysteine). There was virtually complete protection against liver damage in 40 patients treated within eight hours after ingestion (mean maximum serum alanine transaminase activity 27 IU/1). Only one out of 62 patients treated within 10 hours developed severe liver damage compared with 33 out of 57 patients (58%) studied retrospectively who received supportive treatment alone. Early treatment and acetylcysteine also prevented renal impairment and death. The critical ingestion-treatment interval for complete protection against severe liver damage was eight hours. Efficacy diminished progressively thereafter, and treatment after 15 hours was completely ineffective. Intravenous acetylcysteine was more effective than cysteamine and methionine and noticeably free of adverse effects. It is the treatment of choice for paracetamol poisoning.